Possible Role of Large Fluid Intake in Delaying Formation of Encrustations and, thereby, Prolonging Working Life of Memokath Stent for Nearly 14 Years in a Spinal Cord Injury Patient - Subramanian Vaidyanathan; Bakul M. Soni; Peter L. Hughes; Gupreet Singh (The Scientific World Journal)
The Memokath stent has been used in spinal cord injury patients as a reversible alternative to external urethral sphincterotomy, but the stent has a finite lifetime of <2 years before failure in the majority of patients. We report an unusual case of a spinal cord injury patient in whom memokath stent was functioning for almost 14 years. The long life span of the Memokath in this patient was probably due to this person's habit of drinking around 5 l of fluids a day. Large fluid intake resulted in high urine output and, consequently, deceased the risk of urine infections and delayed formation of encrustations around the stent. Although this case represents an unusual length of time for a Memokath stent to have been in place and functioning, caution should be exercised against the long-term use of Memokath stents. Memokath stents do not get absorbed into the mucosa unlike urolume stents and, therefore, are prone to stone formation. Further, Memokath stents have not yet been approved in the U.S. either for bladder outlet obstruction or detrusor-sphincter dyssynergia. This case is also a reminder to health professionals that if a tetraplegic patient, in whom a Memokath stent has been deployed for treatment of detrusor-sphincter dyssynergia, presents with autonomic dysreflexia, encrustations blocking the lumen of the stent or calculus formation around the stent should be considered as possible reasons for autonomic dysreflexia.